TNFα induces matrix metalloproteinase-9 expression in monocytic cells through ACSL1/JNK/ERK/NF-kB signaling pathways - Al-Roub, Areej; Akhter, Nadeem; Al-Rashed, Fatema; Wilson, Ajit; Alzaid, Fawaz; Al-Mulla, Fahd; Sindhu, Sardar; Ahmad, Rasheed (Scientific reports, 2023)
Studies have established the association between increased plasma levels of matrix metalloproteinase (MMP)-9 and adipose tissue inflammation. Tumor necrosis factor α (TNFα) was elevated in obesity and is involved in the induction of MMP-9 in monocytic cells. However, the underlying molecular mechanism was incompletely understood. As per our recent report, TNFα mediates inflammatory responses through long-chain acyl-CoA synthetase 1 (ACSL1). Therefore, we further investigated the role of ACSL1 in TNFα-mediated MMP-9 secretion in monocytic cells. THP-1 cells and primary monocytes were used to study MMP-9 expression. mRNA and protein levels of MMP-9 were determined by qRT-PCR and ELISA, respectively. Signaling pathways were studied using Western blotting, inhibitors, and NF-kB/AP1 reporter cells. We found that THP-1 cells and primary human monocytes displayed increased MMP-9 mRNA expression and protein secretion after incubation with TNFα. ACSL1 inhibition using triacsin C significantly reduced the expression of MMP-9 in the THP-1 cells. However, the inhibition of β-oxidation and ceramide biosynthesis did not affect the TNFα-induced MMP-9 production. Using small interfering RNA-mediated ACSL1 knockdown, we further confirmed that TNFα-induced MMP-9 expression/secretion was significantly reduced in ACSL1-deficient cells. TNFα-mediated MMP-9 expression was also significantly reduced by the inhibition of ERK1/ERK2, JNK, and NF-kB. We further observed that TNFα induced phosphorylation of SAPK/JNK (p54/46), ERK1/2 (p44/42 MAPK), and NF-kB p65. ACSL1 inhibition reduced the TNFα-mediated phosphorylation of SAPK/JNK, c-Jun, ERK1/2, and NF-kB. In addition, increased NF-κB/AP-1 activity was inhibited in triacsin C treated cells. Altogether, our findings suggest that ACSL1/JNK/ERK/NF-kB axis plays an important role in the regulation of MMP-9 induced by TNFα in monocytic THP-1 cells.